Risk factors for early mortality in patients with carbapenem-resistant Acinetobacter baumannii bacteraemia. (December 2022) - Lee, Chan Mi; Kim, Chung-Jong; Kim, Seong Eun; Park, Kyung-Hwa; Bae, Ji Yun; Choi, Hee Jung; Jung, Younghee; Lee, Seung Soon; Choe, Pyoeng Gyun; Park, Wan Beom; Kim, Eu Suk; Song, Je Eun; et al.
Highlights: We identified risk factors associated with EM and LM in CRAB bacteraemia. CRAB bacteraemia with high severity will progress to a rapidly fatal course. The only independent risk factor for EM was the severity of illness. LM was associated with both severity of illness and specific sites of infection. ABSTRACT: Objectives: Although many deaths due to carbapenem-resistant Acinetobacter baumannii (CRAB) bacteraemia occur within a few days after the onset of bacteraemia, risk factors for early mortality (EM) have not been deeply investigated. We aimed to determine the risk factors for EM and the difference between risk factors associated with EM and late mortality (LM) in CRAB bacteraemia. Methods: Clinical information on all patients with CRAB bacteraemia in 10 hospitals during a 1-year period was collected. Among the cases with mortality within 30 days, EM and LM were defined as death within 3 and more than 5 calendar days from the first positive blood culture, respectively. Results: In total, 212 CRAB bacteraemia cases were included in the analysis. Of 122 (57.5%) patients with 30-day mortality, EM was observed in 75 (61.5%) patients and LM in 39 (32.0%) patients. The proportion of severe sepsis or septic shock, Pitt score, and Sequential Organ Failure Assessment (SOFA) score was significantly higher in patients with EM than those with LM. Although urinary tract infection as the site of infection and the severity of illness were independent predictors of LM, only factors representing the severity of illness were independent risk factors for EM. Conclusion: Our results suggest that a large proportion of CRAB bacteraemia with high severity progresses to a rapidly fatal course, regardless of the underlying diseases or source of infection. Further studies might be needed to investigate the microbiological factors associated with CRAB and pathogen-host interaction in patients with EM.